2021
DOI: 10.1111/ped.14480
|View full text |Cite
|
Sign up to set email alerts
|

NUDT15 polymorphism in healthy children with Bai nationality in Yunnan of China

Abstract: Background Thiopurine methyltransferase (TPMT) polymorphism is one of the causes of the toxicity of thiopurines, but this is rarely seen in Asian populations. Rather, the nucleoside diphosphate‐linked X‐component motif 15 (NUDT15) gene is frequently linked to mercaptopurine (MP) intolerance and myelotoxicity in children with acute lymphoblastic leukemia (ALL) in East Asians; however, little is known about the NUDT15 polymorphism in healthy children, especially in ethnic minorities in China. Methods A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…To clarify the distribution of NUDT15 variants in Chinese ethnic minority populations, we conducted a two-by-two comparison of the c.55_56insGAGTCG, c.52G > A, and c.415C > T variant frequencies in seven ethnic groups: Korean ( 23 ), Japanese ( 24 ), Chinese Han, Bai ( 25 ), Uighur, Kirghiz, and Dai, of which Bai is also an ethnic minority in China. The allele frequency of NUDT15 c.55_56insGAGTCG was 5.6% in Korea ( 23 ), 5.4% in Japan ( 24 ), 6.4% in Chinese Han, and 5.6% in Chinese Bai ( 25 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To clarify the distribution of NUDT15 variants in Chinese ethnic minority populations, we conducted a two-by-two comparison of the c.55_56insGAGTCG, c.52G > A, and c.415C > T variant frequencies in seven ethnic groups: Korean ( 23 ), Japanese ( 24 ), Chinese Han, Bai ( 25 ), Uighur, Kirghiz, and Dai, of which Bai is also an ethnic minority in China. The allele frequency of NUDT15 c.55_56insGAGTCG was 5.6% in Korea ( 23 ), 5.4% in Japan ( 24 ), 6.4% in Chinese Han, and 5.6% in Chinese Bai ( 25 ).…”
Section: Resultsmentioning
confidence: 99%
“…To clarify the distribution of NUDT15 variants in Chinese ethnic minority populations, we conducted a two-by-two comparison of the c.55_56insGAGTCG, c.52G > A, and c.415C > T variant frequencies in seven ethnic groups: Korean ( 23 ), Japanese ( 24 ), Chinese Han, Bai ( 25 ), Uighur, Kirghiz, and Dai, of which Bai is also an ethnic minority in China. The allele frequency of NUDT15 c.55_56insGAGTCG was 5.6% in Korea ( 23 ), 5.4% in Japan ( 24 ), 6.4% in Chinese Han, and 5.6% in Chinese Bai ( 25 ). We found that the c.55_56insGAGTCG variant was significantly less frequent in the Uighur and Kirghiz ethnic groups than in the other ethnic groups, and the frequency of variation at this site in the Dai ethnic group was not significantly different from that of the other ethnic groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to a study by Pu et al ., 5 the Bai people, the second largest minority in Yunnan province of China, have a high frequency of the NUDT15 variants, accounting for ~2% of homozygous variants. As shown in Figure 1, the allele frequency of NUDT15 hypomorphic variants varies according to race, and the Asian and Hispanic populations have a higher frequency of NUDT15 whereas TPMT variants are high frequency in other races.…”
Section: Figmentioning
confidence: 99%